Assessment of functional recovery in patients with ACL injuries managed conservatively versus surgically: A comparative observational study. - Karri , Dr . Venkatesh; Adicharla , Dr.Rajendar; Dr. Sravankumar Kamarapu; Boddeda , Dr Geetha Sindhuja; Dr. Dubasi Vydehi (Student’s Journal of Health Research Africa, 2025)
Background: Anterior cruciate ligament injury is a leading cause of knee instability that compromises physical activity and quality of life. Although surgical reconstruction remains the gold standard for restoring knee stability in young and active individuals, conservative treatment continues to be employed in patients with lower activity levels or surgical contraindications. This study evaluated functional outcomes, return to activity, instability, and complications among ACL-injured patients managed conservatively or surgically. Methods: A comparative observational study was conducted on 100 patients with ACL injuries, divided equally into conservative (n = 50) and surgical (n = 50) groups. Baseline demographics, injury characteristics, and management details were recorded. Functional outcomes were assessed using the International Knee Documentation Committee (IKDC) and Lysholm scores at baseline, six months, and 11 months. Return to pre-injury activity, instability episodes, and complications were analyzed. Statistical tests included Student’s t-test and Chi-square, with p < 0.05 considered significant. Results: Baseline characteristics, including mean age (27.6 ± 5.4 vs. 26.9 ± 6.1 years) and gender distribution, were comparable between groups (p > 0.05). At 11 months, surgically managed patients demonstrated significantly higher IKDC (85.1 ± 7.6 vs. 70.4 ± 8.2) and Lysholm scores (88.6 ± 6.9 vs. 74.3 ± 8.4) (p < 0.001 for both). Return to pre-injury sports was achieved in 62% of surgical versus 34% of conservative cases (p = 0.01). Instability episodes were more frequent with conservative care (28% vs. 10%, p = 0.02). Minor complications included donor-site pain (10%) and superficial infection (4%) in the surgical group. Conclusion: Surgical reconstruction of ACL injuries yielded superior functional outcomes, greater return-to-sport rates, and fewer instability episodes compared with conservative management. Conservative treatment remains reasonable for patients with limited functional demands. Recommendations: Multicentric studies with larger cohorts and extended follow-up are warranted to strengthen evidence and refine individualized treatment strategies.